Chinese pension fund investment efficiency: Evidence from CNCSSF stock holdings - Gunnar Lang; Yu Shen; Xian Xu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
China's pension system is facing a large gap of more than one trillion RMB. The investment efficiency of the social security fund therefore receives widespread attention in academic circles. We collected data of stocks held by the Chinese National Council for Social Security Fund (CNCSSF) from 2004 to 2012 to research the stocks' investment efficiency, distinguishing between direct investment by the CNCSSF and entrusted investment by fund companies. The results indicate that both components of the Chinese Social Security Fund investment have efficiency drawbacks. Direct investment by the CNCSSF does not obtain excess returns, while entrusted investment reaches an annual excess return of 4.32 percent because more private information is available to fund companies than to the CNCSSF during asset allocation. Further analyses of this paper find, however, that the Chinese Social Security Fund has a significant market-stabilizing effect, which is almost three times stronger than the market-stabilizing effect of entrusted investment. In general, entrusted investment performs better than direct investment with regard to investment efficiency, while direct investment performs better in terms of market stabilization.
urn:nbn:de:bsz:180-madoc-358509
Keywords: G11; G14; G23; 330; Pension fund investment; Performance evaluation; Chinese pension funds